EVALUASI TEKNIK BUDIDAYA YANG MEMPENGARUHI PRODUKSI TANAMAN STRAWBERRY (Fragaria vesca) DI BERASTAGI KABUPATEN KARO - Hutauruk, Sixtus; Ginting, Erika Afulina Br; Sitohang, Nurdin (AGROSUSTAIN, 2023)
This study aims to collect information on strawberry (Fragaria vesca) cultivation techniques and find out good strawberry (Fragaria vesca) cultivation techniques based on cultivation and production techniques. The research was carried out in several villages in Berastagi District, Karo Regency. This research was started from March to April 2022. The number of samples in this study were 21 strawberry farmers. Data analysis was carried out descriptively and used multiple linear regression analysis using the t (partial) test, the F test (simultaneous), and the R2 test (Determination). Based on the results of the evaluation carried out, it can be stated that the strawberry cultivation technique was carried out and affected the production of strawberry production, namely the Mencir variety, plant age> 8 months, width 60 cm, bed height 35-45, transplanting age 2 months, compost + fertilization + special fertilization, routine pruning once a month, and regular watering during the rainy season. Overall the harvest color, fruit color, size, and taste have a significant effect on the durability of the strawberry.